2017
DOI: 10.1159/000480637
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Expression Level of a Heterogeneous Gene Inserted in LIPI-1 of the <b><i>Listeria ivanovii</i></b> Genome Relies on Its Insertion Orientation

Abstract: Due to its capability to multiply in either phagocytic or nonphagocytic cells, and to subsequently elicit a robust cellular immune response, Listeria ivanovii (LI) is thought to be feasible for developing bacteria-based live attenuated vaccines. We previously generated several recombinant LI strains expressing Mycobacterium tuberculosis antigens. Since the expression level of heterogeneous protein was sometimes very low, we attempted to elucidate the principle of heterogeneous protein expression in such recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
1
Order By: Relevance
“…This result was inconsistent with a previous study where a LI strain was found to be capable of colonizing the liver of mice [Hof and Hefner, 1988]. We conclude this to be due the integration of heterologous gene which diminished the virulence of LI, since a similar LI vectored vaccine candidate expressing the Rv0129c protein of M. tuberculosis showed a higher LD 50 value than its parent strain [Liu et al, 2017].…”
Section: Discussioncontrasting
confidence: 99%
“…This result was inconsistent with a previous study where a LI strain was found to be capable of colonizing the liver of mice [Hof and Hefner, 1988]. We conclude this to be due the integration of heterologous gene which diminished the virulence of LI, since a similar LI vectored vaccine candidate expressing the Rv0129c protein of M. tuberculosis showed a higher LD 50 value than its parent strain [Liu et al, 2017].…”
Section: Discussioncontrasting
confidence: 99%